Increasing The Role of Bhabinkamtibmas in Order to Prevent The Occurrence of Child Crimes in The Police Metro Pancoran Mas Polres Metro Depok - Nabil Khairullah (Advances in Police Science Research Journal, 2021)
This research is motivated by the rise of criminal cases committed or with child victims that every year the number is increasing in the area of Police Law Metro Pancoran Mas. This is what makes cases involving children begin to be a concern and must be resolved. The handling of the rise of the case is to improve the role of Bhabinkamtibmas in the description of duties and responsibilities daily, control the implementation of bhabinkamtibmas tasks to be more targeted and refer to the written rules and review what factors affect the role of Bhabinkamtibmas in carrying out its duties. This research method is done with qualitative approach. Using descriptive research methods of analysis. Data collection techniques with interviews, observations, and document studies. Meanwhile, the technique of validity and reliability of data from research results using data triangulation techniques, using data analysis in the form of data reduction, data presentation, as well as conclusion and verification. Based on the results of the research shows that the still imperfect implementation of the role of Bhabinkamtibmas analyzed with the theory of prevention and concept of the role of polmas, and Perkap No. 3 of 2015, as well as the level of public knowledge about child crime is analyzed with communication theory. The factors that hinder the implementation time of tasks, priority programs, and completeness of facilities. The impact of bhabinkamtibmas presence is still less felt by the community because it is constrained by COVID-19, the material that mostly contains about resilient villages, and overrides the appeal of kamtibmas, especially crimes involving children. According to the results of the research that has been obtained by researchers, researchers provide advice to the Police Chief, Kasat Binmas and the Chief of Police as the head to pay more attention to the role of Bhabinkamtibmas in understanding the task of counseling and pay attention to the problems of facilities and infrastructure needed, in addition to the materials and recommendations determined so as not to contain about covid-19 countermeasures and resilient villages.